Evaluating Potential Effects of an Industrial Road on Winter Habitat of Caribou in North-Central Alaska - Wilson, Ryan R.; Gustine, David D.; Joly, Kyle (ARCTIC, 2014)
Worldwide, some caribou (Rangifer tarandus) populations are experiencing declines due partially to the expansion of industrial development. Caribou can exhibit behavioral avoidance of development, leading to indirect habitat loss, even if the actual footprint is small. Thus, it is important to understand before construction begins how much habitat might be affected by proposed development. In northern Alaska, an industrial road that has been proposed to facilitate mining transects a portion of the Western Arctic caribou herd’s winter range. To understand how winter habitat use might be affected by the road, we estimated resource selection patterns during winter for caribou in a study area surrounding the proposed road. We assessed the reductions of habitat value associated with three proposed routes at three distance thresholds for disturbance. High-value winter habitat tended to occur in locally rugged areas that have not burned recently and have a high density of lichen and early dates of spring snowmelt. We found that 1.5% to 8.5% (146–848 km2) of existing high-value winter habitat in our study area might be reduced in quality. The three alternative routes were only marginally different. Our results suggest that the road would have minimal direct effects on high-value winter habitat; however, additional cumulative impacts to caribou (e.g., increased access by recreationists and hunters) should be considered before the full effects of the road can be estimated. À l’échelle mondiale, certaines populations de caribous (Rangifer tarandus) connaissent des déclins partiellement attribuables à l’expansion industrielle. Pour des raisons de comportement, le caribou peut éviter le développement, ce qui entraîne une perte d’habitat indirecte, et ce, même si la place réellement occupée est petite. Par conséquent, il est important de comprendre, avant même que des travaux de construction ne soient amorcés, dans quelle mesure l’habitat sera touché par les travaux proposés. Dans le nord de l’Alaska, une route ...